2016
DOI: 10.1177/1420326x16672509
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance and environmental quality of typical railway passenger stations in northern China

Abstract: In recent 20 years, the energy performance of public buildings has attracted substantial attention due to the potential for significant energy savings. As semi-open structures, railway passenger stations are noticeably distinct from other public buildings. This paper investigated current energy consumption situation of 36 railway passenger stations in northern China. The energy consumption of the railway passenger stations was divided into high, medium and low levels, with the annual average energy use indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It should be noticed that the linear relationship between operational GHG emissions and area is not evident, as investigated in [16] the regarding correlation between energy consumption and station area. In energy simulations of this study, energy use from the waiting room accounts approximately for 60% of total energy consumption from all operating rooms.…”
Section: Reduction Potential Analysis Of Life Cycle Ghg Emissionsmentioning
confidence: 96%
See 2 more Smart Citations
“…It should be noticed that the linear relationship between operational GHG emissions and area is not evident, as investigated in [16] the regarding correlation between energy consumption and station area. In energy simulations of this study, energy use from the waiting room accounts approximately for 60% of total energy consumption from all operating rooms.…”
Section: Reduction Potential Analysis Of Life Cycle Ghg Emissionsmentioning
confidence: 96%
“…Research concentrating on railway station buildings, especially the high speed type, is relatively limited; some of the existing literature takes into account reduction measures for energy consumption that are directly correlated to operational emissions, such as: the relationship between energy consumption and passenger flow density [16]; energy efficiency measures on performance parameters of a building envelope, area ratio of skylight and sun shading mode [17]; energy saving approaches that place greater emphasis on the reduction of air infiltration [18]; triadic relation among lighting comfort level and lighting energy consumption [19]; intelligent control strategies as feasible energy saving solutions [20]; and energy efficient analysis on construction scale, space design, function layout, and operation mode [21,22]. Energy potential in conventional stations or HSRS has been analyzed in different domestic regions.…”
Section: Ghg Emission Reduction Strategies For Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important and special branch of public buildings, traffic transportation buildings like railway stations have characteristics of large space span, various functions, high density of people, and long operation time of air conditioning system. Energy consumption and energy-saving approaches of these kind of buildings are also quite different from those of common public buildings [10].…”
Section: Introductionmentioning
confidence: 98%
“…Energy consumption of traditional railway stations in China is about 101-423 kWh/(m 2 ·a). Calculation results showed that the energy consumption of the HVAC system accounted for 30-60% of the total energy consumption of the station, while the lighting system and the elevator system had a percentage of 10-20% and 5-10% [10,11], respectively. Li et al [12] studied the energy-saving potential and a higher ceiling height will have more obvious chimney effect in winter, which may increase the heating load in winter.…”
Section: Introductionmentioning
confidence: 99%